A bi-objective model with sequential search algorithm for optimizing network-wide train timetables. (January 2019) - Tian, Xiaopeng; Niu, Huimin
Highlights: A bi-objective model is proposed for optimizing network-wide train timetables. The relation for timetables, transfer schemes and number of connections is analyzed. Sequential search algorithm is developed to solve the proposed model. Abstract: This study focuses on how to optimize train timetables with transfer synchronization for a high-speed rail network. Aiming at network-based and synchronization-oriented train operations, a bi-objective integer programming model integrated with irregular headways is proposed to maximize the number of connections and minimize the total transfer waiting time for one day. This study also reveals an interactive relationship for timetables, transfer schemes and number of connections. By optimizing the two objectives sequentially, we develop a novel heuristic search algorithm to solve the proposed model. Specifically, an initial solution is obtained by independently optimizing the first objective, and the improved timetables are iteratively searched to minimize the total waiting time under the maximum number of transfer connections. We also put forward a set of numerical experiments to demonstrate the effectiveness and availability of the proposed approach.